Revisiting metabolic syndrome: The importance of weight management - Dicky L Tahapary (World Nutrition Journal, 2022)
Metabolic syndrome is an increasing major health problem worldwide, including Indonesia. More than one third of adult Indonesian population suffered from metabolic syndrome. Metabolic syndrome itself is actually a clustering of risk factors which increase the risk for diabetes mellitus and cardiovascular diseases in the future. Therefore, prompt management of metabolic syndrome is required to prevent the development of diabetes mellitus dan cardiovascular diseases.